2010
DOI: 10.1111/j.1439-0426.2010.01562.x
|View full text |Cite
|
Sign up to set email alerts
|

Fine structure, motility and cryopreservation of spotted sea bass, Lateolabrax maculatus (Moronidae, Teleostei), spermatozoa

Abstract: Both transmission-and scanning electron microscopy were used to investigate the fine structure of spermatozoa of the spotted sea bass (Lateolabrax maculatus). The spermatozoa are of the ect-aquasperm type, with a head lacking acrosome, midpiece, and tail regions. The centriolar complex is situated outside the nuclear fossa and the flagellum is parallel to the base of the nucleus. A midpiece, containing four mitochondria, extends from the posterior end of the nucleus and encircles the root of the flagellum. A p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 27 publications
0
3
0
Order By: Relevance
“…After 5 h, the samples were dehydrated with graded ethanol, followed by four changes of tert-butyl alcohol (TBA). Semen were then criticalpoint dried and gold coated (Wu et al, 2007;Gwo, 2010). The ultrastructure of sperm was observed under a JSM-S3400N scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…After 5 h, the samples were dehydrated with graded ethanol, followed by four changes of tert-butyl alcohol (TBA). Semen were then criticalpoint dried and gold coated (Wu et al, 2007;Gwo, 2010). The ultrastructure of sperm was observed under a JSM-S3400N scanning electron microscope.…”
Section: Methodsmentioning
confidence: 99%
“…Major problems which affect short-term storage of milt are temperature, gaseous exchange, microbial attack and desiccation (Fauvel et al, 1998;Pereira 1999;Fauvel et al, 2012). Reports show that anaerobic storage of sperm at 4°C resulted in low motility and aerobic storage (in oxygen) at the same temperature showed high fertility rate (94%) after 216 h (Saad et al, 1988;Chereguini et al, 1997;Gwo, 2010). The enhanced, sperm motility; motility duration and viability recorded in the present study can be correlated to the presence of oxygen in the medium as reported above.…”
Section: Milt Collectionmentioning
confidence: 99%
“…Then specific cryoprotectants are added. For example, the dilution of Lateolabrax maculeatus sperm in a simple NaCl solution with either 5 or 10% dimethyl sulfoxyde (DMSO) was sufficient to protect it at freezing (Gwo, ).…”
Section: Introductionmentioning
confidence: 99%